Who begins: transfer and transformation of administrative culture from the League of Nations to the World Health Organization - Schacht, Anastassiya (Administory, 2022)
This article reconstructs the course of WHO-establishing activities and analyses how the WHO’s administrative culture was a continuation of its...
Online veröffentlicht: November 2024
Gesehen am 12.05.2025